(untitled) (Alberta Journal of Educational Research, 2007)
Students in small rural schools in British Columbia face barriers to accessing senior science courses. A case study employing questionnaire and interview methods sought the perspectives of principals, teachers, and students in the affected schools on this issue. Interpretive data analysis revealed the following barriers as key factors that affect students’ successful access to senior science courses: staffing at the school, availability of specialist teachers, trusting relationships between students and teachers, and the school and local cultures. The study considers these factors as constituting a border between students and school science, the crossing of which mediates students’ access to the culture of school science.